Comparative Effectiveness of Exclusive Breastfeeding Versus Formula Feeding on Infant Growth and Development - Husnul Hayat, Khurram Nawaz, Rizwan Mahmood, Muhammad Usman Rafique, Sanwal Sardar Nawaz, Imran Yasin (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Infant nutrition during the first six months of life plays a pivotal role in shaping long-term growth, health, and neurodevelopmental outcomes. Objective: To compare the effectiveness of exclusive breastfeeding versus formula feeding on infant growth and developmental outcomes. Methodology: This cross-sectional comparative study was conducted at Department of Pediatric Medicine, Avicenna Medical College & Hospital Lahore from 1st January 2023 to 30th June 2023. A total of 555 infants aged 6 to 12 months were enrolled using non-probability consecutive sampling. Participants were divided into two groups: group A was treated with exclusively breastfed (n = 278) and group B treated with exclusively formula-fed (n=277). Data were collected through structured questionnaires, anthropometric measurements, and developmental assessments using the Denver Developmental Screening Test II. Results: The mean age was 8.6±1.9 months. Formula-fed infants had higher mean body weight (8.55±1.15 kg) compared to breastfed infants (8.20±1.05 kg; p=0.004), but also a higher proportion above the 90th weight-for-age percentile (13.0% vs. 5.0%; p=0.001). Exclusively breastfed infants demonstrated superior developmental performance across gross motor (93.2% vs. 88.1%), fine motor (94.6% vs. 89.2%), language (90.3% vs. 83.8%), and social domains (92.1% vs. 85.2%), with overall developmental delay significantly lower in this group (6.1% vs. 14.8%; p = 0.001). Logistic regression analysis identified exclusive breastfeeding (AOR = 2.14; 95% CI: 1.25–3.65) and maternal education (AOR = 1.76; 95% CI: 1.09–2.83) as independent predictors of normal growth and development. Conclusion: The exclusive breastfeeding during the first six months of life leads to healthier growth patterns and superior developmental outcomes compared to formula feeding. Despite formula feeding providing adequate nutrition, it was associated with rapid weight gain and higher risk of developmental delay. Keywords: Exclusive breastfeeding, Formula feeding, Infant growth, Developmental outcomes